Spectrum of Pediatric Dermatosis and Seasonal Variation - Asma Khalid, Tariq Mehmood (Journal of Islamic International Medical College, 2021)
Objective: To determine the pattern of skin disorders seen among children attending a Medical College Hospital. Study Design: A descriptive Study . Place and Duration of Study: The study was conducted at Dermatology Dept. Pakistan Railway Hospital from Dec 2011 to July 2012. Materials and Methods: All children 13 years and below attending the Dermatology OPD with skin diseases were included between the period of December 2011 to July 2012. A detailed history was taken; thorough clinical examination was done and was supported by investigations wherever necessary. The diseases were tabulated based on the various groups and results were analysed. Results: A total of 2357 cases (boys 1037; girls 1320) with different dermatosis were included in the study.. Most of the disorders were seen between 1 to 5 years of age. The most common dermatoses were bacterial infections (26.21 %) and infestations(13.70% ) followed by viral and fungal infections ( 11.96% , 11.41%). Seasonal variation among childhood dermatosis were also noted during summer and winter. Total of 996 patients were included in the study. Most common dermatosis seen among children during summer were bacterial infections(41.16 %) followed by miliaria ( 12.55), viral and fungal infections (11%) napkin dermatitis (10.84) and infestations ( 9.63). During winter most common dermatosis seen were infestations (26.26 %), seborrheic dermatitis( 24.45%) bacterial and fungal infections and pityriasis alba ( 9.31 %). Among other dermatosis seen were papular urticaria, vitiligo, alopecia areata, papulosquamous disorders, acne and genetic disorders (0.76%). Conclusion: In the present setting bacterial infections and infestations are the most common pediatric dermatoses followed by viral and fungal infections and eczematous eruptions.